Relationships between digital screen time, dietary behaviour, lifestyle patterns and Body Mass Index in university students during the COVID-19 pandemic - Lim, See Meng; Liew, Wen Huey; Wong, Jyh Eiin (Penerbit Universiti Kebangsaan Malaysia, 2024)
The COVID-19 pandemic has changed individual's dietary habits and lifestyles. University students are at risk of developing weight problems due to changes in eating and lifestyle habits imposed by the switch to online learning. Therefore, this study aimed to determine the relationships between dietary behaviour, lifestyle, digital screen time and body mass index (BMI) among university students during the COVID-19 pandemic. A cross-sectional study was conducted with 253 university students between October and November 2021. Data were collected on sociodemographic, anthropometrics, dietary behaviour, screen time and lifestyle habits using an online questionnaire. Laptop and desktop screen time used for entertainment was significantly lower in students who studied online (p<0.05). Most students skipped main meals (71.9%) but snacked between meals (85.8%). Students who underwent online classes (online students) consumed more fruits and vegetables than students undergoing hybrid learning (p=0.035). Compared to online students, hybrid students dined out more often during the pandemic (p<0.001), bought meals from outside (p<0.001) and ate with friends (p<0.001). There were weak negative relationships between BMI and consumption of fruits and vegetables (r=-0.199, p<0.01) and carbohydrate sources (r=-0.185, p<0.01) and frequency of physical activity (r=-0.194, p<0.01). There was a weak positive correlation between BMI and frequency of dinner consumption (r=0.203, p<0.01) and home-based workouts (p<0.01). In conclusion, dietary behaviour and lifestyle patterns during the pandemic were associated with BMI among Klang Valley university students. These findings suggest that promoting healthy lifestyles among university students is important for improving body weight management and overall well-being.